Genome sequencing reveals the role of rare genomic variants in Chinese patients with symptomatic intracranial atherosclerotic disease. Issue 3 (8th December 2021) - Shi, Mengmeng; Leng, Xinyi; Li, Ying; Chen, Zihan; Cao, Ye; Chung, Tiffany; Ip, Bonaventure YM; Ip, Vincent HL; Soo, Yannie OY; Fan, Florence SY; Ma, Sze Ho; Ma, Karen; et al.
Abstract : Objectives: The predisposition of intracranial atherosclerotic disease (ICAD) to East Asians over Caucasians infers a genetic basis which, however, remains largely unknown. Higher prevalence of vascular risk factors (VRFs) in Chinese over Caucasian patients who had a stroke, and shared risk factors of ICAD with other stroke subtypes indicate genes related to VRFs and/or other stroke subtypes may also contribute to ICAD. Methods: Unrelated symptomatic patients with ICAD were recruited for genome sequencing (GS, 60-fold). Rare and potentially deleterious single-nucleotide variants (SNVs) and small insertions/deletions (InDels) were detected in genome-wide and correlated to genes related to VRFs and/or other stroke subtypes. Rare aneuploidies, copy number variants (CNVs) and chromosomal structural rearrangements were also investigated. Lastly, candidate genes were used for pathway and gene ontology enrichment analysis. Results: Among 92 patients (mean age at stroke onset 61.0±9.3 years), GS identified likely ICAD-associated rare genomic variants in 54.3% (50/92) of patients. Forty-eight patients (52.2%, 48/92) had 59 rare SNVs/InDels reported or predicted to be deleterious in genes related to VRFs and/or other stroke subtypes. None of the 59 rare variants were identified in local subjects without ICAD (n=126). 31 SNVs/InDels were related to conventional VRFs, and 28 were discovered in genes related to other stroke subtypes. Our study also showed that rare CNVs (n=7) and structural rearrangement (a balanced translocation) were potentially related to ICAD in 8.7% (8/92) of patients. Lastly, candidate genes were significantly enriched in pathways related to lipoprotein metabolism and cellular lipid catabolic process. Conclusions: Our GS study suggests a role of rare genomic variants with various variant types contributing to the development of ICAD in Chinese patients.